Blackmoore : a proper romance - Donaldson, Julianne (Shadow Mountain, 2013)
Having decided she will never marry, Kate Worthington plans to escape her meddlesome family by travelling to India. Her mother agrees on the condition that she gets--and rejects--three marriage proposals. To fulfill her end of the bargain Kate travels to the manor of Blackmoore in northern England, where her plans go awry.